Low Amplitude Boom-and-Bust Cycles Define the Septoria Nodorum Blotch Interaction - Phan, Huyen T. T.; Jones, Darcy A. B.; Rybak, Kasia; Dodhia, Kejal N.; Lopez-Ruiz, Francisco J.; Valade, Romain; Gout, Lilian; Lebrun, Marc-Henri; Brunner, Patrick C.; Oliver, Richard P.; Tan, Kar-Chun (Frontiers in Plant Science, 2020)
Septoria nodorum blotch (SNB) is a complex fungal disease of wheat caused by the Dothideomycete fungal pathogen Parastagonospora nodorum. The fungus infects through the use of necrotrophic effectors (NEs) that cause necrosis on hosts carrying matching dominant susceptibility genes. The Western Australia (WA) wheatbelt is a SNB “hot spot” and experiences as much as 50% yield loss under favorable conditions. Consequently, SNB has been a major target for breeders in WA for many years. In this study, we assembled a panel of 155 WA P. nodorum isolates collected over a 44-year period and compared them to 23 isolates from France and the USA using 28 SSR loci. The WA P. nodorum population was clustered into five groups with contrasting properties. Eighty percent of the studied isolates were assigned to two core groups found throughout the collection location and time. The other three non-core groups that encompassed transient and emergent populations were found in restricted locations and time. Changes in group genotypes occurred during periods that coincided with the mass adoption of a single or a small group of widely planted wheat cultivars. When introduced, these cultivars had high scores for SNB resistance. However, the field resistance of these new cultivars often declined over subsequent seasons prompting their replacement with new, more resistant varieties. Pathogenicity assays showed that newly emerged isolates non-core are more pathogenic than old isolates. It is likely that the non-core groups were repeatedly selected for increased virulence on the contemporary popular cultivars. The low level of genetic diversity within the non-core groups, difference in virulence, low abundance, and restriction to limited locations suggest that these populations more vulnerable to a population crash when the cultivar was replaced by one that was genetically different and more resistant. We characterise the observed pattern as a low-amplitude boom-and-bust cycle in contrast with the classical high amplitude boom-and-bust cycles seen for biotrophic pathogens where the contrast between resistance and susceptibility is typically much greater. Implications of the results are discussed relating to breeding strategies for more sustainable SNB resistance and more generally for pathogens with NEs.